IMPROVING STUDENTS’ READING COMPREHENSION BY USING INQUIRY CHART STRATEGY TO THE NINTH GRADE STUDENTS OF SMP SWASTA KATOLIK BUDI MURNI 2 MEDAN - Sitinjak, Rahul; Tarigan, Karisma E; Sari, Anna Stasya Prima (Kairos English Language Teaching Journal, 2020)
The aim of this study is to find that Inquiry Chart Strategy works effectively on improving students’ reading comprehension and to know the students’ responses after being taught by using Inquiry Chart Strategy. In order to achieve the objectives of the study, a classroom action research was designed and carried out in this study. The participants of this study are 25 students of class IX-4 of SMP Swasta Budi Murni 2 Medan in the academic year 2018/2019. Test, observation sheet and field notes were used as the instruments for collecting data. The result of the study showed significant improvement of the students’ skill in reading. It is proven by the students’ mean score of each test: pre test is 50 with 12%, formative test is 73,92 with 72%, and post test is 87,6 with 92%. And then the percentage of the students’ improvement score from pre-test to post-test was 75.2%. And the total percentage of strongly agree was 55.2%. In addition, the analysis result of the observation sheet and field notes showed that Inquiry Chart Strategy changed the students’ learning behaviour became better than before. They were more enthusiastic during the learning teaching process in each cycle. Based on the result of those study instruments, it can be concluded that using Inquiry Chart Strategy gives the improvement to the students’ reading comprehension. This strategy is suggested to English teacher to apply it in teaching learning reading in order to improve students’ reading comprehension. The writer also suggests to other writers to explore other studies on Inquiry Chart Strategy to improve the students’ reading comprehension and try to apply this technique in different language skills.